2006
DOI: 10.1029/2005jc003277
|View full text |Cite
|
Sign up to set email alerts
|

Bidecadal variability in the intermediate waters of the northwestern subarctic Pacific and the Okhotsk Sea in relation to 18.6‐year period nodal tidal cycle

Abstract: On the basis of historical oceanographic data, we investigated the long‐term variations of the intermediate waters in the four regions in the northwestern subarctic Pacific: Oyashio, Okhotsk Sea Mode Water, Upstream Oyashio and East Kamchatka Current. We found bidecadal oscillations in these water properties that are synchronized with the 18.6‐year period nodal cycle. In periods when the diurnal tide is strong, the following characteristics are found: Apparent oxygen utilization and phosphate are low in Oyashi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
88
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(97 citation statements)
references
References 29 publications
(46 reference statements)
9
88
0
Order By: Relevance
“…The non-anthropogenic CO 2 contribution dominantly accounted for the enhanced acidification of intermediate water rather than anthropogenic CO 2 uptake, but our value might be an overestimate. This is because the long-term trends and bi-decadal oscillations of AOU in subsurface waters in the northwestern subarctic Pacific Ocean have been reported (ex., Ono et al, 2001;Osafune and Yasuda, 2006;Watanabe et al, 2008, Takatani et al, 2012. In our data, collected during 1997-2011, AOU varies on a shorter than bi-decadal cycle and the AOU increase on 26.9σ θ (1.8 ± 0.4 µmol kg −1 yr −1 ) was twice that from 1968 to 1998 in the Oyashio region near the western subarctic gyre (0.8 ± 0.3 µmol kg −1 yr −1 ) (Ono et al, 2001).…”
Section: +063(16/170aou)mentioning
confidence: 74%
See 1 more Smart Citation
“…The non-anthropogenic CO 2 contribution dominantly accounted for the enhanced acidification of intermediate water rather than anthropogenic CO 2 uptake, but our value might be an overestimate. This is because the long-term trends and bi-decadal oscillations of AOU in subsurface waters in the northwestern subarctic Pacific Ocean have been reported (ex., Ono et al, 2001;Osafune and Yasuda, 2006;Watanabe et al, 2008, Takatani et al, 2012. In our data, collected during 1997-2011, AOU varies on a shorter than bi-decadal cycle and the AOU increase on 26.9σ θ (1.8 ± 0.4 µmol kg −1 yr −1 ) was twice that from 1968 to 1998 in the Oyashio region near the western subarctic gyre (0.8 ± 0.3 µmol kg −1 yr −1 ) (Ono et al, 2001).…”
Section: +063(16/170aou)mentioning
confidence: 74%
“…We obtained a decadal time series by combining data from the two stations, because the duration of sampling at each individual station data was not sufficient. Typically, in this region the minimum temperature (T min ) in the water column is associated with the remnant of the mixed layer water in the preceding winter and occurs at about 26.5σ θ (∼ 100 m), and the maximum temperature occurs at about 27.1σ θ (∼ 370 m) (e.g., Ueno and Yasuda, 2000;Osafune and Yasuda, 2006). Each year, the surface mixed layer reached its maximum depth from mid-March to early April (Fig.…”
Section: Data and Analysesmentioning
confidence: 99%
“…The tidal constituents are known to change seasonally (e.g., Kang et al, 2002), interannually (e.g., Munk et al, 1965), and secularly (e.g., Ray, 2006, and references therein) although their mechanisms are still poorly understood. Even the theoretically expected 18.6-year nodal modulation has recently been paid attention in relation to bi-decadal climate changes (e.g., Osafune and Yasuda, 2006;Ray, 2007). It is expected that such OBTM data in excess of 10-year durations will yield valuable information for tidal studies.…”
Section: Discussionmentioning
confidence: 99%
“…A half-century-scale warming (Hill et al 2003;Itoh 2007;Nakanowatari et al 2007) and decadal-scale variability (Osafune and Yasuda 2006) have recently been discovered within the intermediate-water temperature in the Okhotsk Sea. Since the warming signal is significant along the pathway of the DSW, and is accompanied by a decrease in dissolved oxygen, Nakanowatari et al (2007) suggested that the warming is caused by a reduction in the production of DSW, and further suggested that this decrease is caused by a reduction in sea ice production during winter.…”
Section: Introductionmentioning
confidence: 99%